DELETERIOUS FUNCTIONAL IMPACT OF ANEMIA ON ADOLESCENTS: A SURVEY STUDY - Devi, Karthiga; Priya, Jothi (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To access the physical work capacity and cognition of underprivileged anemic adolescent, hemoglobin (Hb) of subjects was assessed for the adolescence under 17-20 years of age by undergoing survey. Methods: This is a cross-sectional study, conducted in students of 1st year of Saveetha Dental College. The general information about age, Hb level (Sahli’s method), knowledge about anemia, status of menstruation, and regarding the consumption of various diet factors were recorded on a structured questionnaire. Due to feasibility and cost effectiveness, Hb estimation was done by Sahli’s hemoglobinometer. Results: Our study proved that now a days adolescence is not much more prone to anemia. And mostly 40% of adolescence were having mild anemia. This mild anemia can be improved by dietary intake and bioavailability of iron, nutritional supplementation of iron and folic acid (IFA) tablets, and fortification of edible dietary items with iron. This difference was statistically significant (Chi-square value 4.848, p<0.001). Conclusion: The study was mainly done for adolescence awareness on anemia. Iron deficiency anemia occurs most frequently in adolescence because accelerated physical growth both in boys and girls and menstruation and dieting for fear of obesity in female teenagers. The prevalence of anemia necessitates pragmatic intervention to improve the dietary intake, nutritional supplement of IFA tablets. Keywords: Adolescence, Dietary factors, Knowledge about anemia.